Step * 1 2 1 of Lemma list_decomp_reverse


1. [T] Type
2. T
3. u1 T
4. List
5. ∃x:T. ∃L':T List. ([u1 v] (L' [x]) ∈ (T List))
⊢ ∃x:T. ∃L':T List. ([u; [u1 v]] (L' [x]) ∈ (T List))
BY
((ExRepD THEN InstConcl [x;[u L']]) THEN Auto) }

1
1. Type
2. T
3. u1 T
4. List
5. T
6. L' List
7. [u1 v] (L' [x]) ∈ (T List)
⊢ [u; [u1 v]] ([u L'] [x]) ∈ (T List)


Latex:


Latex:

1.  [T]  :  Type
2.  u  :  T
3.  u1  :  T
4.  v  :  T  List
5.  \mexists{}x:T.  \mexists{}L':T  List.  ([u1  /  v]  =  (L'  @  [x]))
\mvdash{}  \mexists{}x:T.  \mexists{}L':T  List.  ([u;  [u1  /  v]]  =  (L'  @  [x]))


By


Latex:
((ExRepD  THEN  InstConcl  [x;[u  /  L']])  THEN  Auto)




Home Index